Curriculum Innovation in Islamic Education: Embedding Nationalism and Patriotism for Civic Transformation - Bagas Ardhy Surya Kusuma; Nurul Latifatul Inayati (Eastasouth Institute, 2026)
The integration of nationalism and patriotism within Islamic education remains inadequately structured, often relying on implicit pedagogical practices that limit its effectiveness in fostering sustained civic awareness and state defense consciousness. This study aims to develop a transformative curriculum perspective by examining how civic values are embedded within Islamic education and identifying pathways for more systematic integration. Employing a qualitative case study design, the research was conducted at SMAS IT Nur Hidayah Sukoharjo, involving purposively selected teachers and school stakeholders. Data were collected through semi-structured interviews and document analysis, and analyzed using a thematic approach to generate in-depth and contextually grounded insights. The findings reveal that while nationalism and patriotism are conceptually aligned with Islamic values and are present in instructional practices, their integration remains largely implicit, fragmented, and dependent on individual teacher interpretation. Additionally, the absence of explicit curriculum frameworks, measurable learning outcomes, and structured pedagogical models constrains the potential of Islamic education to achieve meaningful civic transformation. However, the study also identifies a strong pedagogical synergy between Islamic ethical principles and civic identity formation, which can serve as a foundation for curriculum innovation. The study contributes to the development of a civic-oriented Islamic education framework that emphasizes explicit value integration, multidimensional learning outcomes, and transformative pedagogical strategies. These findings have important implications for curriculum development, educational policy, and instructional practices, particularly in strengthening national identity, civic responsibility, and social cohesion through religious education.